Recursive allocations and wealth distribution with multiple goods: Existence, survivorship, and dynamics - R. Colacito; Mariano M. Croce; Zhao Liu (Quantitative Economics, 2019)
We characterize the equilibrium of a complete markets economy with multiple agents featuring a preference for the timing of the resolution of uncertainty. Utilities are defined over an aggregate of two goods. We provide conditions under which the solution of the planner's problem exists, and it features a nondegenerate invariant distribution of Pareto weights. We also show that perturbation methods replicate the salient features of our recursive risk-sharing scheme, provided that higher-order terms are included.
Keywords: C62; F37; 330; Recursive preferences; multiple agents; equilibrium